كتاب تعليم اللغة العربية لوزارة الشؤون الدينية في ضوء مبادئ المدخل الاتصالي - Yunaldi Yunaldi; Ela Isnani Munawwaroh; Widian Yusfi Fauziah (Department of Arabic Education - Faculty of Educational Sciences, 2022)
The book is a learning resource for students and sometimes does not always support the educational activities of students on Arabic language communication practices. This research aims to reveal the extent of the representation and presentation of educational activities in the Arabic language teaching book published by the Ministry of Religious Affairs based on the communication approach principles. This research is qualitative with a descriptive analysis that describes the presentation of educational activities based on the principles of Jack Croft Richards' communication approach. The method of data collection used is documentary studies with statistical analysis of the percentage assessment. Based on the results of data analysis and processing by using evaluative innstrument consisting of 17 points, the researcher concluded that the contents of the book were appropriate to the communication approach principles.